2011
DOI: 10.1089/ten.tea.2010.0113
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation of Human Keratinocytes and Cocultured Human Keratinocytes and Fibroblasts in Three-Dimensional Fibrin Constructs

Abstract: Over the last several years, our in vitro and in vivo studies have focused on optimizing the use of fibrin to deliver cells. We have shown that some three-dimensional (3D) fibrin constructs with specific fibrinogen and thrombin concentration support robust proliferation of normal human dermal fibroblasts, whereas different fibrinogen and thrombin concentrations support high mesenchymal stem cell proliferation in 3D fibrin constructs. In this article, we found that normal human epithelial keratinocytes prolifer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 19 publications
3
31
0
Order By: Relevance
“…It is also of interest that ARA290 mitigated the TNF-α-driven inflammatory response, as expression of the Fas receptor (FasR; synonym: CD95, TNFRS6), part of the extracellular apoptotic pathway, was also strongly suppressed. We also investigated the effect of ARA290 on leukocyte adhesion behavior, which is an important factor of tissue infiltration and/or microvascular injury due to interactions with the vascular endothelium (21). TNF-α and interleukin (IL)-1β are known to induce cell adhesion molecules (CAMs) on the surface of the endothelium and circulating leukocytes along with other actions that cause hypercoagulability (22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…It is also of interest that ARA290 mitigated the TNF-α-driven inflammatory response, as expression of the Fas receptor (FasR; synonym: CD95, TNFRS6), part of the extracellular apoptotic pathway, was also strongly suppressed. We also investigated the effect of ARA290 on leukocyte adhesion behavior, which is an important factor of tissue infiltration and/or microvascular injury due to interactions with the vascular endothelium (21). TNF-α and interleukin (IL)-1β are known to induce cell adhesion molecules (CAMs) on the surface of the endothelium and circulating leukocytes along with other actions that cause hypercoagulability (22)(23)(24).…”
Section: Resultsmentioning
confidence: 99%
“…Sese et al reported that keratinocyte proliferation in three-dimensional fibrin constructs was influenced by thrombin concentration. These authors found that the optimal thrombin concentration in fibrin matrices for stimulating keratinocyte proliferation was about 1 U/mL, 43 while the proliferation of fibroblasts was not strongly dependent Figure 8 Immunofluorescence staining of fibronectin produced by dermal fibroblasts. Notes: Fibronectin (green) produced by dermal fibroblasts on poly(lactide-co-glycolic acid) (PLGA) membranes with a fibrin nanocoating (A, B) or on uncoated Plga membranes (C, D) on day 3 (A, C) and on day 7 (B, D) after seeding.…”
mentioning
confidence: 99%
“…However, varying concentrations of fibrinogen and thrombin can influence the morphology and rigidity of the fibrin network, and thereby cell survival and proliferation [38,39]. Based on this observation, Luyckx et al [40] decided to develop a fibrin matrix that would allow survival and proliferation of isolated human ovarian cells by determining the optimal combination of fibrinogen and thrombin.…”
Section: Fibrinmentioning
confidence: 99%